2013
DOI: 10.1051/0004-6361/201118179
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic energy fluxes in sub-Alfvénic planet star and moon planet interactions

Abstract: Context. Electromagnetic coupling of planetary moons with their host planets is well observed in our solar system. Similar couplings of extrasolar planets with their central stars have been studied observationally on an individual as well as on a statistical basis. Aims. We aim to model and to better understand the energetics of planet star and moon planet interactions on an individual and as well as on a statistical basis. Methods. We derived analytic expressions for the Poynting flux communicating magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
335
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(350 citation statements)
references
References 103 publications
(204 reference statements)
15
335
0
Order By: Relevance
“…Therefore, any future models attempting to explain the early UV observation need to include planetary gas in their simulations. The modeling described here does not provide any additional constraints on whether a bow shock exists around close-in exoplanets (see Saur et al 2013 and VJH11a for conflicting arguments) but does show that the bow shock does not produce any observable signature in the UV and optical.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, any future models attempting to explain the early UV observation need to include planetary gas in their simulations. The modeling described here does not provide any additional constraints on whether a bow shock exists around close-in exoplanets (see Saur et al 2013 and VJH11a for conflicting arguments) but does show that the bow shock does not produce any observable signature in the UV and optical.…”
Section: Discussionmentioning
confidence: 80%
“…Saur et al [2013] found the Enceladus interaction to be nearly saturated; i.e., the incident plasma is decelerated to almost complete stagnation, and the currents in the interaction region are at their maximum strength (see Table 1 in that work). Hence, there are two possible explanations for the weakness of the observed magnetic field jumps: on the one hand, it is very likely that Cassini has not yet crossed those regions of the flux tube where the hemisphere coupling currents are strongest.…”
Section: Impact Of the Anti-hall Effectmentioning
confidence: 92%
“…Subsequently, Saur et al [2007], Simon et al [2011b], and Kriegel et al [2011] applied this method to analyze various aspects of the magnetic field perturbations and the asymmetric flow deflection near the plume of Enceladus. Based on the analytical expressions for the electromagnetic fields, Saur et al [2013] and Simon et al [2013] calculated the Poynting flux generated by sub-Alfvénic moon-plasma interactions and by the electromagnetic coupling of exoplanets to their host stars. Saur [2004] also succeeded in solving equation (4) for an elliptically shaped obstacle with constant conductances.…”
Section: Simon Model Of Moon-plasma Interactions 7211mentioning
confidence: 99%
“…We therefore stress that r M here refers to a characteristic distance to the point where magnetic pressure equilibrium exists, which places an upper limit on the magnetospheric size, with the size at the nose being smaller if the stellar wind ram pressure is also taken into account. We note that the relative orientation of the stellar magnetic field with respect to the orientation of the planetary magnetic moment plays an important role in shaping the open-field-line region on the planet (e.g., Ip et al 2004;Zieger et al 2006;Kopp et al 2011;Sterenborg et al 2011;Saur et al 2013). Our purely magnetic pressure balance (Eq.…”
Section: Interaction Between the Planet And The Corona Of Its Host Starmentioning
confidence: 99%
“…On the stellar side, factors such as the thermal pressure, magnetic pressure (P B, ) and the ram pressure resulting from the relative motion between the planet and the coronal material can all contribute to setting the pressure equilibrium. The stellar-wind properties determine, for example, whether Earth-type magnetospheres surrounded by bow shocks or Ganymede-type magnetospheres with Alfvén wings are formed (Ip et al 2004;Zarka 2007;Kopp et al 2011;Sterenborg et al 2011;Saur et al 2013). To quantitatively evaluate this, the stellar wind density, temperature, magnetic field, and the relative velocity of the planet are required together with planetary magnetic characteristics.…”
Section: Interaction Between the Planet And The Corona Of Its Host Starmentioning
confidence: 99%